2018
DOI: 10.1186/s12889-018-5502-x
|View full text |Cite
|
Sign up to set email alerts
|

SMS reminders to improve adherence and cure of tuberculosis patients in Cameroon (TB-SMS Cameroon): a randomised controlled trial

Abstract: BackgroundIn Cameroon, the National Tuberculosis Control Program that applies selective directly observed treatments faces difficulties in its implementation for a lack of resources, leading to only 65% of patients with sputum smear-positive pulmonary tuberculosis being cured after 6 months of treatment. This study aimed to evaluate the effectiveness of daily Short Message Service reminders to increase adherence and the proportion of adult tuberculosis patients cured after 6 months of treatment.MethodsA simple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(101 citation statements)
references
References 35 publications
1
78
2
4
Order By: Relevance
“…This cannot happen if one has no phone and so may lead to loss to follow up. Mobile phone technologies (mHealth), specifically SMS reminders have improved patient outcomes in other health service delivery settings [38][39][40] but were comparable to the standard of care for HIV retention in other settings [41,22,42]. It is however important to note that the level of interaction between provider and patient, and subset of activities under mHealth greatly determine the effectiveness of particular interventions.…”
Section: Plos Onementioning
confidence: 99%
“…This cannot happen if one has no phone and so may lead to loss to follow up. Mobile phone technologies (mHealth), specifically SMS reminders have improved patient outcomes in other health service delivery settings [38][39][40] but were comparable to the standard of care for HIV retention in other settings [41,22,42]. It is however important to note that the level of interaction between provider and patient, and subset of activities under mHealth greatly determine the effectiveness of particular interventions.…”
Section: Plos Onementioning
confidence: 99%
“…Only eight studies [41][42][43][44][45][52][53][54] were found to be fitted for the pooled estimation of the effect of mobile phone messaging on successful TB treatment outcome. Six studies were exclude with the following reasons.…”
Section: Quantitative Synthesis Of Evidencesmentioning
confidence: 99%
“…Using mobile phone text messages (SMS) to remind patients with chronic conditions, enhances treatment adherence and reduces transportation costs [15]. Although several studies have evaluated SMS messaging's effectiveness for TB treatment [16][17][18][19][20], the body of evidence remains limited and the need for further studies is warranted.…”
Section: Introductionmentioning
confidence: 99%